The Role of Media in the Promotion of Divine Religions and Contemporary Communication Methods - Riaz, Muhammad; Batool, Naila (Journal of Islamic and Religious Studies, 2021)
The divine religions are concerned with the promotion of true knowledge of Allah Almighty. These religions, in their broadest sense, are spread over a wide area of the world, and with each passing day, their propagation and transmission is expanding. It has been a tradition for centuries that whether it is human beings or religions, they have needed media for the truth of their word. It is certain that the divine religions also made full use of the prevailing media of their time and succeeded in conveying their ideas and thoughts to many people. The preaching struggle of the divine religions did not span a single century but a long span of centuries, the scale of which we cannot determine at present. However, some aspects can be pointed out historically. Two important sections are highlighted in this article. The role of the media in the promotion of divine religions. The contemporary communication methods and aspects of competition between the nations of the world, especially between the Indian subcontinent and the West. In addition to the divine religions, this article also discusses the mode of communication of non-divine religions and gives a brief overview of their methods.